Lack of reactivation of tuberculosis in patients with psoriasis treated with secukinumab in a real-world setting of latent tuberculosis infection - Matteo Megna; Cataldo Patruno; Maria Rita Bongiorno; Alessio Gambardella; Claudio Guarneri; Caterina Foti; Serena Lembo; Francesco Loconsole; Gabriella Fabbrocini (Journal of Dermatological Treatment)
Background Some biologics for psoriasis, especially anti-tumor necrosis factor (TNF)-α therapies, may re-activate latent tuberculosis (TBC) infection with consequent morbidity and mortality. However, there is a low reported incidence of conversion to positive TBC status among patients with psoriasis treated with second-generation biologic therapies, particularly anti-interleukin (IL)-17 therapies such as secukinumab.Objectives To evaluate the safety profile of secukinumab in psoriasis patients with latent TBC infection.Methods Real-life data were collected by retrospective chart review on patients with moderate-to-severe psoriasis who showed positivity for TBC screening at baseline and underwent secukinumab treatment for psoriasis at six Italian centers. Patients received secukinumab 300 mg at week 0/1/2/3/4, then every 4 weeks.Results Fifty-nine patients were enrolled; 30.5% also had psoriatic arthritis and other comorbidities were common. At baseline, the mean psoriasis duration was 14.5 years. Ten (17%) patients did not undergo prophylaxis before starting secukinumab. Conversely, isoniazid ± rifampicin or rifampicin alone prophylaxis was administered in 49/59 (83.1%) patients. After a mean treatment duration of 84 weeks, there were no cases of TBC reactivation and no unexpected safety signals.Conclusions Secukinumab use over an extended period was safe in psoriasis patients with latent TBC, even in patients who did not receive chemoprophylaxis.